Political entrepreneurs in social media: Self-monitoring, authenticity and connective democracy. The case of Íñigo Errejón - Maria Iranzo-Cabrera; Andreu Casero-Ripollés (Heliyon, 2023)
Political entrepreneurs seek to mobilise public opinion and access large audiences who are not directly interested in politics, but are exposed to the digital environment. The aim of this research was to analyse how these figures promote experimental communication uses on channels far removed from political activity. We focused on Twitch, a successful platform for promoting entertainment and learning in the video games field. To do so, we conducted a significant case study, that of Íñigo Errejón, a Spanish male Member of Parliament, in 2021 through 18 live streamings that lasted 1223 min. We specifically described the conception and use of Twitch, measured the audience's impact, analysed the accountability exercise through this platform and evaluated the deliberative quality of conversation with users. To conclude, we identified three novel contributions of Twitch to digital political communication: self-monitoring, insofar as the elected politician himself proactively exercises accountability to the public without a third party intervening; the activation of mediated authenticity as a key value in the political actor's public construction; promoting connective democracy, which would help those sectors not used to employing political information to take an interest in it by detecting attention being paid to their needs and questions.